2010
DOI: 10.1111/j.1365-2125.2010.03698.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F2 rs2108622: a minor significant genetic factor of warfarin dose in Han Chinese patients with mechanical heart valve replacement

Abstract: KeywordsCYP2C9, CYP4F2, Chinese, mechanical heart valve replacement, VKORC1, warfarin ---------------------------------------------------------------------- Received WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Genetic polymorphisms of VKORC1 and CYP2C9 are known to influence warfarin dosage.• Recent studies among Caucasians showed that polymorphisms of CYP4F2 also play a role in warfarin pharmacogenetics.• The contribution of CYP4F2 variants to the variability inwarfarin dose requirement in Chinese subjects rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 29 publications
(40 reference statements)
5
65
3
1
Order By: Relevance
“…Perini et al (2010) studied a mixed population and reported no significant effect of CYP4F2 polymorphism on warfarin dose, which contradicts with the results of two studies conducted on Chinese populations (Cen et al, 2010;Li et al, 2012). The results of this study showed that CYP4F2 had a significant effect on warfarin dose.…”
Section: Impact Of Genetic Factors On Steady-state Dose Of Warfarincontrasting
confidence: 98%
See 1 more Smart Citation
“…Perini et al (2010) studied a mixed population and reported no significant effect of CYP4F2 polymorphism on warfarin dose, which contradicts with the results of two studies conducted on Chinese populations (Cen et al, 2010;Li et al, 2012). The results of this study showed that CYP4F2 had a significant effect on warfarin dose.…”
Section: Impact Of Genetic Factors On Steady-state Dose Of Warfarincontrasting
confidence: 98%
“…The results of this study showed that CYP4F2 had a significant effect on warfarin dose. CYP4F2 mutations might increase the required dose of warfarin, which is consistent with that reported by Cen et al (2010) and Li et al (2012). The heterozygous mutations of CYP4F2 had little influence, whereas the homozygous mutations of CYP4F2 could significantly influence the steady-state warfarin dose.…”
Section: Impact Of Genetic Factors On Steady-state Dose Of Warfarinsupporting
confidence: 89%
“…An association between the CYP4F2 variant (rs2108622) and warfarin dose was subsequently confirmed in a meta-analysis involving more than 9000 participants from 30 studies [80] . Although the association of CYP4F2 is significant, the effect size is much lower than those contributed of VKORC1 and CYP2C9 in Han Chinese in South China [81] , and its clinical use …”
Section: Warfarinmentioning
confidence: 99%
“…The VKORC1 and CYP2C9 genotype results were validated using control samples that had been genotyped as part of a previous study. 14 CYP4F2 genotypes were validated by regenotyping 26 samples in duplicate by PCR-restriction fragment length polymorphism analysis as described by Cen et al 15 …”
Section: Genotypingmentioning
confidence: 99%